The Effect of Cultivar and Stage of Growth on the Fermentation, Aerobic Stability and Nutritive Value of Ensiled Quinoa - Şaban Yılmaz; İbrahim Atış; İbrahim Ertekin (Journal of Agricultural Sciences)
Quinoa has the potential to be an important alternative source of silage as a forage crop. However, there is limited information on the ensiling of quinoa in the literature. This study investigates the silage fermentation quality, nutritive value and aerobic stability of quinoa cultivars harvested at different plant growing stages. The experiment was carried out in the experimental area of the Hatay Mustafa Kemal University, Faculty of Agriculture in the 2019 and 2020 growing seasons. The experiment was laid out in a split plot with a randomized block design with three replications, the three main plots were based on harvesting times (flowering, milky and dough stages) and the five sub-plots were based on cultivars (Mint Vanilla, Cherry Vanilla, French Vanilla, Red Head and Titicaca). Traits such as pH, ammonia nitrogen, lactic acid bacteria (LAB), LA, acetic acid (AA), butyric acid (BA), propionic acid, ethanol (EtOH), dry matter (DM), neutral detergent fiber, acid detergent fiber, acid detergent lignin, crude protein, ash, ether extract, water soluble carbohydrate (WSC) and relative feed value were analyzed in order to determine silage fermentation quality and nutritive value. In addition, all silages were evaluated in terms of aerobic stability. In reference to the interaction effects, pH, ammonia nitrogen, LAB, AA, BA and EtOH, the silage fermentation quality parameters were between 3.83-4.16, 5.57-14.83%, 4.69-5.80 log10cfu/g DM, 1.37-2.10%, 0.32-0.51% and 0.79-1.63, respectively. On the other hand, DM, ADF, ash and WSC changed between 21.95-33.36%, 22.39-28.36%, 15.41-17.70% and 2.35-9.50%, respectively, as silage nutritive composition features. The carbon dioxide production values of silages exposed to air were between 5.49 g/kg and 10.26 g/kg according to interactions. Among the evaluated quinoa cultivars, cv. Titicaca and cv. French Vanilla provided superior results in terms of fermentation quality compared to other cultivars. It was also determined that it would be more appropriate to harvest these superior quinoa cultivars during the dough stage for quality silage. Among the silages, the cv. Titicaca had the best aerobic stability. As a result of this study, it was concluded that cv. French Vanilla and cv. Titicaca should be harvested during the dough stage in order to obtain better silage quality. According to the results of this study, it was deduced that the quinoa plant could be an alternative ensiling crop.